2016
DOI: 10.1080/14786419.2016.1266349
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric profile & antimicrobial activities of leaf extract of Calotropis procera and Calotropis gigantea

Abstract: Calotropis procera and Calotropis gigantea are medicinal plant having therapeutic value. The leaf extracts of C. procera have been investigated, its pharmacological actions in detail and leaf extracts of C. gigantea were not studied till date. The objective of present work was to find the bioactive constituents present in the ethanolic leaf extract of C. procera and C. gigantea to evaluate their antibacterial and anifungal activities. The major phytochemical groups in C. procera ethanolic leaf extracts were fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Previously, the anti-candidal action of AgNPs was found to be improved using a combination with commercially available amphotericin b against five Candida species [23]. Thus, our data identified C. gigantea leaf extract as a source of bioactive antifungal compounds that could contribute in the extracellular synthesis of AgNPs, and has a stronger antifungal action than the previously designated antifungal effect [14,56,57].…”
Section: Discussionmentioning
confidence: 54%
“…Previously, the anti-candidal action of AgNPs was found to be improved using a combination with commercially available amphotericin b against five Candida species [23]. Thus, our data identified C. gigantea leaf extract as a source of bioactive antifungal compounds that could contribute in the extracellular synthesis of AgNPs, and has a stronger antifungal action than the previously designated antifungal effect [14,56,57].…”
Section: Discussionmentioning
confidence: 54%
“…The major phytochemical groups reported in the leaf extracts of C. procera are fatty acid ethyl esters (21.4%), palmitic acid esters (10.2%), linoleic acids (7.4%), and amino acids (8.1%) (Pattnaik et al, 2017). High-Performance Liquid Chromatography (HPLC) analysis of the leaves and bark ascertained the presence of total phenolic content (20.41-100.18 gallic acid equivalent mg g −1 dry weight), total flavonoid content (IC 50 18.33-92.92 catechin equivalent mg g −1 dry weight), sinapic acid (17.3 ± 2.11 to 9586.44 ± 0.78 mg kg −1 ), vanillic acid (9.43 ± 0.21 to 5051.7 ± 18.47 mg kg −1 ) and protocatechuic acid (2.46 ± 0.40 to 139.05 ± 1.37 mg kg −1 ) (Mehmood et al, 2020).…”
Section: Phytochemistry Metabolic Profilementioning
confidence: 99%
“…In addition, digestive properties [13] have been attributed to its flowers. Pattnaik et al [14] reported that these medicinal properties arise from phytochemical groups observed in leaf extracts of C. procera: fatty acid ethyl ester, palmitic acid ester, linoleic acid, and amino acids. It is worth mentioning that, to our knowledge, all of the antibacterial and medicinal activities of C. procera derivatives have been associated with ethanolic extracts from parts of the plants.…”
Section: Introductionmentioning
confidence: 99%